Professional Development of Elementary School English Teachers in the Teacher Professional Education Program (PPG): A Qualitative Study of Teaching English to Young Learners (TEYL) Practices - Siti Maria Ulfa; Tera Athena; Zainal Arifin (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
This study aims to explore the impact of the in-service Teacher Professional Education (PPG) Program on improving the pedagogical competence of English teachers at the elementary school level, specifically within the context of the Teaching English to Young Learners (TEYL) approach. With the policy establishing English as a compulsory subject in elementary schools under the 2024 Curriculum, which will be implemented simultaneously in 2027, the need for teachers with pedagogical competence appropriate to the characteristics of early childhood learners is becoming increasingly urgent. This study employed a qualitative approach. The first stage involved a survey of 25 elementary school English teachers to obtain an overview of their professional development practices. The survey results then served as the basis for selecting three case study participants for further research through classroom observations and in-depth interviews. The research results indicate that most teachers have participated in various forms of ongoing professional development, including formal training, teacher learning communities, webinars, and digital technology-based independent learning. The PPG program significantly contributed to improving teachers' understanding of lesson planning, authentic assessment, learning differentiation, and the implementation of learner-centered learning approaches. Furthermore, teachers who participated in PPG demonstrated improved skills in integrating TEYL principles, such as the use of communicative activities, educational games, songs, visual media, and contextual learning appropriate to the characteristics of elementary school students. However, this study also identified several challenges, including limited experience teaching English in elementary schools, a lack of appropriate learning resources, and the need for ongoing post-PPG mentoring to ensure the implementation of acquired competencies in teaching practice. This research provides recommendations for policymakers to strengthen the design of elementary school English teacher training through more explicit integration of pedagogical competencies and TEYL principles within the PPG program.